Action Real-Time Strategy Gaming Experience Related to Enhanced Capacity of Visual Working Memory - Yao, Yutong; Cui, Ruifang; Li, Yi; Zeng, Lu; Jiang, Jinliang; Qiu, Nan; Dong, Li; Gong, Diankun; Yan, Guojian; Ma, Weiyi; Liu, Tiejun (Frontiers in Human Neuroscience, 2020)
Action real-time strategy gaming (ARSG) – a major genre of action video gaming (AVG) – has both action and strategy elements. ARSG requires attention, visual working memory, sensorimotor skills, team cooperation, and strategy-making abilities, thus offering promising insights into the learning-induced plasticity. However, it is yet unknown whether ARSG experience is related to the development of visual working memory (VWM) capacity. Using both behavioral and event-related potential (ERP) measurement, this study tested whether ARSG experts had larger VWM capacity than non-experts in a change detection task. The behavioral results showed that ARSG experts had higher accuracy and larger VWM capacity than non-experts. In addition, the ERP results revealed that the difference wave of contralateral delay activity (CDA) component (size 4 – size 2) elicited by experts was significantly larger than non-experts, suggesting that the VWM capacity was higher in the experts than non-experts. Thus, the findings suggested that prolonged ARSG experience is correlative with the enhancement of VWM.